Принцип таємного голосування як одна із складових демократичного інституту виборів в Україні - Бучин, Микола (Видавництво Національного університету "Львівська політехніка", 2009)
The important of a democratic principle of secret ballot is analyzed in this article. Author also developed the level of observance of a democratic principe of secret ballot during electoral practice in Ukraine.
Keywords: democratic principles of election; secret ballot; electoral campaign